2010
DOI: 10.1016/j.bbi.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Minimal penetration of lipopolysaccharide across the murine blood–brain barrier

Abstract: LPS given peripherally or into the brain induces a neuroinflammatory response. How peripheral LPS induces its effects on brain is not clear, but one mechanism is that LPS crosses the blood-brain barrier (BBB). Alternatively, LPS acts outside the BBB by stimulating afferent nerves, acting at circumventricular organs, and altering BBB permeabilities and functions. Here, we labeled LPS with radioactive iodine (I-LPS) and co-injected it with radioactively labeled albumin (I-Alb) which acted as a vascular space mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
228
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(246 citation statements)
references
References 45 publications
12
228
0
1
Order By: Relevance
“…On the other hand, a new study carried out on rats injected with radioactive-iodine-labeled LPS (I-LPS) suggests that some measurable amount of LPS crosses the BBB (Banks and Robinson, 2010). The results of these studies could have been affected by insufficiently sensitive LPS detection methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a new study carried out on rats injected with radioactive-iodine-labeled LPS (I-LPS) suggests that some measurable amount of LPS crosses the BBB (Banks and Robinson, 2010). The results of these studies could have been affected by insufficiently sensitive LPS detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in vivo studies performed on rats showed that peripherally injected LPS previously labeled with radioactive iodine 125 crossed the BBB. The brain uptake of circulating LPS was found to be low but measurable (Banks and Robinson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This treatment regimen causes progressive loss of neurons in the substantia nigra in male mice [47]. Under normal conditions peripheral LPS passage across the blood-brain barrier is low [48] and therefore does not induce brain inflammation directly. However, systemic LPS induces hepatic TNFα synthesis and secretion and subsequent TNFα-receptor-dependent signal transduction to the brain, where TNFα synthesis is further amplified [49].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, another report provides evidence that nigral injection of VEGF to mice disrupted the BBB permeability and induced dopaminergic neuronal death in the ventral mesencephalon (VM) (Chen et al, 2008a). Acute systemic injection of LPS to rats either directly or indirectly can also cause functional breakdown of the BBB resulting in granulocyte infiltration and activation of parenchymal microglia (Banks and Robinson, 2010;Perry, 2004) which contribute to the degeneration of dopaminergic neurons in the SNpc (Brochard et al, 2009;Dutta et al, 2008).…”
Section: Blood Brain Barrier Permeabilitymentioning
confidence: 99%